Red Rubies Colored Gold: Aureation in the Līlātilakam (ലീലാതിലകം ) - Aaron Charles Sherraden (University of Texas at Austin, 2014)
The Līlātilakam of late fourteenth-century Kerala represents an attempt to grammatically and aesthetically solidify an ongoing aureate tradition—to borrow the concept from its associations with Middle English authors such as Chaucer—blending the Keraḷa-bhāṣā (old Malayalam) with Sanskrit lexical and poetic systems. That tradition takes shape as a literary and dramatic language known as Maṇipravāḷam—maṇi, the red ruby of Keraḷa-bhāṣā, and pravāḷam, the red coral of Sanskrit. Ideally words of the two language traditions blend together in a seamless and unnoticeable mixture, importing Sanskrit poetics as the basis of its aesthetics. The author of the Līlātilakam adds his linguistic venture to the long line of theoretical contemplation in Sanskrit poetics, but one that is notably distant from Tamil poetic and literary traditions. A primary motivation behind developing Maṇipravāḷam lies in the desire to distinguish Keraḷa-bhāṣā and the region where it is spoken from the socio-linguistic dominance of Tamil. We can see how the author situates his work with Sanskrit poetics by looking at his descriptions of the key concept of rasa, or poetic sentiment, and his encouragement of literary dialogue between two groups of trained cultural elites: the poets and the connoisseurs, the sahṛdayas.